Sensory Evaluation of Mayonnaise Preparred with Vegetable Oil and Egg Yolk of Local Chicken (Faculty of Animal Science Universitas Brawijaya, 2013)
The objectives of current research were to find out the precise combination between concentrations of vegetable oils (65%; 70%; 75%) and chicken egg of local chicken (6%; 9% and 12%) which produced mayonnaise with an acceptance of panelist. The results showed that the best treatment obtained from a combination of vegetable oil 75% concentration by concentration of chicken egg of local chicken 9% Key words: fat, fatty acids, carotene, shrimp waste